TANGGUNG JAWAB PERUSAHAAN INDUK LION GROUP TERHADAP PRAKTIK DISKRIMINASI PENJUALAN KAPASITAS KARGO - Siti Bianca Zahara; Heru Pringgodani Sanusi (Fakultas Hukum Universitas Trisakti, 2021)
KPPU decided that Lion Air, Batik Air, Wings Air, and Lion Parcel (Lion Group Airlines), through closed agreements, have practiced discrimination against Custody Service Companies (PJT) in certain Geographic Markets. The formulation of the problem is how the responsibility of PT Langit Esa Oktagon and PT Lion Group as the parent company for the closed agreement by Lion Group Airlines as a subsidiary that is indicated as a discriminatory practice and how the form of responsibility that can be given by PT Langit Esa Oktagon and PT Lion Group as the parent company. The method used is normative, descriptive writing nature, primary and secondary data types, qualitative data analysis, and deductive logic conclusions. Based on the results of research, discussion and conclusions; UUPT, Anti Monopoly Law, and other related regulations, then to business actors can be applied the doctrine of Single Economy Entity (SEE) which considers one Group Company as a unified economic entity so that there is joint responsibility between companies in it, so that in this case PT Langit Esa Oktagon and PT Lion Group can be subject to criminal sanctions based on Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition.